Mechanical losses in internal combustion engines: analysis, diagnostics and experimental assessment methods - Kuzmenko, Serhii (National Technical University "Kharkiv Polytechnic Institute", 2025)
This paper explores the origin, classification, and quantitative evaluation of mechanical losses in internal combustion engines (ICEs). These losses are responsible for a significant portion of the fuel consumption and influence the engine’s performance, efficiency, and durability. Both theoretical and experimental methods are reviewed, with special emphasis on practical diagnostic techniques applicable to modern automotive and tractor engines.
Keywords: mechanical losses; internal combustion engine; experimental methods; fuel efficiency; tribology; diagnostics; modeling